INVESTIGATING STUDENTS’ CRITICAL THINKING SKILL IN CHEMICAL EQUILIBRIUM USING THE DISCOVERY LEARNING - Fajarisma Izzatul Nadia; Endang Widjajanti Laksono (Universitas Negeri Yogyakarta, 2021)
This study aimed to determine the effect of discovery learning on the students’critical thinking skill. The research was a comparative study with 64 students of 11th grade that were randomly selected from senior high school in Yogyakarta. The data of critical thinking was collected through the critical thinking test instrument. Face content and construct validity conducted as initial step in developing the instrument before the test was used to measure students’ critical thinking skill toward the research sample. The instrument went through the RD for examining its validity and reliability using the Partial Credit Model with the result of validity showed 8 of 10 items fit with model. The study analysis was conducted using t-test and descriptive analysis. The results of this study show there was a significant difference in students’ critical thinking between the experiment and control group. The profile results of critical thinking skill indicate that indicators of problem identification were better compared to other indicators learning.